Quand écrire sur les murs passe de la clandestinité au marché de l’art : Exit Through the Gift Shop, un vertige de vrai et de faux pour une histoire du street art - Marie Bouchet (Les Cahiers de Framespa)
Exit Through the Gift Shop: A Banksy Film (2010) appears like a documentary on the history of street art. It was made by the world-famous, though mysterious, street artist Banksy and, as its title indicates, it is characterized by a reflection on the transformation of street art, an illegal, nocturnal art form that made its way into museums and the private collections of Hollywood stars in the late 2000s. This «mockumentary», as some journalists call it, plays with blurring the limits between truth and lies, uses mise en abyme effects and reversals, and stages the shifting of power that has occurred around street art.